Current status of research on influencing factors of sleep complaints at home and abroad (国内外睡眠抱怨的影响因素研究现状) - WU Siyue (吴斯悦); LIANG Mijun (梁蜜峻); XU Lingyan (徐林燕) (中西医结合护理)
This paper reviewed the domestic and overseas studies on overview, influencing factors, assessment tools of sleep complaints, in order to arouse the attention of domestic medical staff on sleep complaints, reduce the risk of sleep complaints, and provide reference for the development of sleep complaints related research in China. (本文对睡眠抱怨的概述、影响因素、评估工具进行综述, 旨在引起医护人员对睡眠抱怨的重视, 降低睡眠抱怨的发生风险, 为睡眠抱怨相关研究的开展提供参考依据。)